Pharmacotherapy, etiopathogenesis, and diagnostics of bronchial asthma: assessment of the level of senior medical students’ knowledge. Comparison of the ASSA-I AND ASSA-II project results - Bontsevich, Roman A.; Adonina, Anna V.; Gavrilova, Anna A.; Vovk, Yana R.; Shchurovskaya, Kristina V.; Kutsenko, Darya I.; Mikhno, Alina V.; Korokin, Mikhail V.; Peresypkina, Anna A. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Bronchial asthma (BA) is an incurable chronic disease that can become controlled after the appointment of rational and reasonable therapy. Due to the prevalence of this pathology, a patient with asthma can be met by a doctor of any specialty, so every clinician should have basic knowledge in the field of this nosology. We aimed to analyze the results of the first and second stages of the ASSA project and to determine the differences in the levels of senior students’ knowledge in the field of BA. Material and Methods. The article presents the results of an anonymous multicenter ASSA study (the full name of the project is “Assessment of senior medical students in the field of bronchial asthma”, “ASSA” is a partial acronym) to assess the level of senior medical students’ knowledge in the field of etiology, pathogenesis, diagnosis, and treatment of BA. The first stage of this study (2014-2016) involved 521 students from 7 cities in Russia. For the second stage (2017-2019), the results from 358 senior students from 6 cities of Russia and Ukraine were received and analyzed. The method of anonymous questioning was used in this study, for which an original questionnaire was developed based on current clinical guidelines. Results and Discussion. Over the five years of the study, the level of students' knowledge remains above the average, without significant changes. The following questions in the two stages of the project caused the greatest difficulties in the respondents: question No.1 (the definition of BA), No.2 (a trigger of an asthma attack), No.3 (a key factor of asthma pathogenesis). Positive dynamics were observed on question No.11 (the basic treatment of moderate asthma), No.7 (the levels of BA control) and No.4 (the laboratory and instrumental markers of BA).